Clipping and Companding Technique for BER and PAPR Reduction in OFDM System - Vinay Singal, Nitin Saroha, (International Journal of Scientific Research and Management (IJSRM), 2015)
Peak to Average Power Ratio (PAPR) is one of most detrimental aspects in any wireless communication system using multicarrier modulation technique like OFDM, which cause power degradation and spectral spreading. Due to the simplest way for PAPR reduction, clipping technique has been proposed and seems to be promising for use in commercial system. In this paper, we mainly focus on Amplitude clipping and filtering method. Later in this paper, simulation result shows the PAPR and BER performance with clipping and filtering with different clipping ratios. The BER of the original OFDM signal is approximate 10−3 at SNR = 10 dB. With clipping, BER is increased to just higher than 10−2 at the SNR = 10 dB and the BER performance improves a little bit with filtering.